Gambaran ketertarikan masyarakat Kelurahan Tuminting terhadap pengembangan usaha burung puyuh sebagai daya dukung ekonomi di masa new normal - Kiroh, H.J.; Sondakh, E.H.B.; Rimbing, S.C. (ZOOTEC, 2021)
REFLECTION OF INTEREST OF THE TUMINTING VILLAGE COMMUNITY TOWARDS THE DEVELOPMENT OF QUAIL BUSINESS AS A SOLUTION TO SUPPORT THE FAMILY ECONOMY IN THE NEW NORMAL. The purpose of the study was to explore the level of interest of the Tuminting Village community towards the development of quail business as a solution to support the family economy and to find an overview of the basic understandings that the Tuminting Village community had known if their quail farming business would be developed with simple technology. The variables measured in the community were: level of education, community work and income, community interest in quail business, understanding of village officials on quail farming. The data or information collected was analyzed simply by calculating the percentage and then presented in the form of a bar chart, while the results of other observations would be described descriptively, including describing things that were seen and received directly from the community as the object under study. The results of the research on public interest in quail business showed that there were around 32.02% interested in developing quail cultivation in the New Normal Covid-19 period. The level of basic understanding of the Tuminting Village community towards quail development efforts from the results of the study was shown to be 51.09%. Meanwhile, the understanding of village officials in supporting quail farming by the community illustrated that more than 56.25% did not understand, but they strongly support the development of quail cultivation and the value was around 84.75%. The conclusion was that although the number of people who did not understand was still very high, they still have a high interest in participating and in developing the quail farming business as a support for the family economy during the New Normal Covid-19 period.Keywords: Community interest, village officials, quail, new normal covid-19